Archives Deschâtelets-NDC (2023)
Les Archives Deschâtelets-NDC sont les archives historiques et administratives des missionnaires Oblats. Elles ont pour mission d’acquérir, traiter, conserver, améliorer l’accessibilité et diffuser…
Keywords: _imprimé

American Baptist Historical Society (American Baptist Historical Society, 2023)
The American Baptist Historical Society (ABHS) holds the archives and serves as the historical interpreter of a major religious denomination — American Baptist Churches USA — made up of 4,900 churches and 1.2 million people. ABHS archival collections include records from many different Baptist organizations in North America and around the world. As the oldest Baptist historical society (founded in 1853) with the largest and most diverse collection of Baptist historical material, our holdings are of irreplaceable value to church, national, and global history. ABHS serves as keeper of the record of the modern missionary movement. Our shelves hold unparalleled resources documenting African-American church associations, women’s work, local church and association minutes, and the social gospel movement. We publish the oldest Baptist journal, Foundations, interpreting for modern readers the lives and issues of the past that shape who we are today.
Keywords: _open access